Analisis Representasi Kekuasaan Politik Film Dirty Vote Dalam Perspektif Norman Fairclough - Nur Vania Fitra; Joko J. Prihatmoko Prihatmoko (Spektrum, 2026)
Dirty Vote is an effective mass communication medium in delivering social and political criticism, especially of democratic practices in Indonesia ahead of the 2024 elections. Released during the quiet period, this film raises allegations of fraud and power intervention in the electoral process. This research aims to analyze the representation of political power in Dirty Vote from Norman Fairclough's perspective. This research uses a qualitative methodological framework to analyze six excerpts of scenes as representations of political power. The results of the analysis show that language in films is used strategically to shape public opinion and convey ideological messages about certain figures and institutions. Discourse practices reflect the process of film production and distribution in a political context full of interests, while socio-cultural practices reveal the relationship between film narratives and power structures in society. Thus, Dirty Vote does not only function as a documentary work, but also as a tool of discourse criticism that dismantles the dominance of power and voices public aspirations for a more ethical and transparent democracy. Keywords: Critical Discourse Analysis, Norman Fairclough, Representation of Power, Documentary Film, Dirty Vote